Mobile Application for Computer Laboratory Maintenance in Institute of Informatics and Business (IIB) Darmajaya - Yuni Arkhiansyah; Rio Kurniawan; Sulyono Sulyono; Chairani Chairani; Rian Sefriadi (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The problem statement of this study was that checking and monitoring process in the computer laboratory of Institute of Informatics and Business (IIB) Darmajaya was less optimal because it was still carried out manually. This caused a difficulty for the head and assistants of the computer laboratory because the written data on paper were vulnerable, and easy to lose and scatter. According to this problem, an application was needed not only for the assistants of the computer laboratory who used it to record the checked-list data but also for the head of the computer laboratory who used it to monitor the readiness of the laboratory in real time. It was expected that the application was able to facilitate the checking and monitoring process for the assistants of the computer laboratory. Moreover, the application was expected to facilitate the head of the computer laboratory to monitor the readiness of the computer laboratory by looking at checked lists data stored in the database.Keywords: Monitoring, Real Time, Computer Laboratory